Astronomia no ensino de ciências por meio de uma Ilha Interdisciplinar de Racionalidade de acordo com a BNCC - Werle, Cíntia (My University, 2022)
This research work presents the development and results of an online pedagogical intervention in Science Teaching, with students from Elementary School II, about Astronomy. The Interdisciplinary Islands of Rationality (IIR) method, proposed by Fourez (1997), was chosen to promote scientific and technological literacy (ACT) of these students through the teaching of Astronomy. This research had as a general objective: to analyze the application of the IIR method in the online format in promoting the teaching of Astronomy in the final years of Elementary School. And, as specific objectives: to promote the teaching of Astronomy through the Interdisciplinary Islands of Rationality method; develop the attributes of ACT by students: communication, autonomy and mastery of the topic; and create a didactic guide for teachers on the teaching of Astronomy using the IIR method, in accordance with the BNCC assumptions. The activities were developed with a 9th grade class, from a school in a rural area of the state of Rio Grande do Sul (RS), during the year 2020. The research is within the line " Foundations and Educational Strategies in the Teaching of Science and Mathematics", proposed for the master?s degree in Science and Mathematics Teaching at the University of Caxias do Sul. This research is of applied nature, qualitative approach and, in relation to the procedures, it is a pedagogical intervention. The results achieved, with the activities developed, demonstrate that the development of the attributes of the ACT occurred by the students through the construction of the IIR: autonomy in the execution of the activities, communication with the working groups and during the presentations, and mastery of the theme chosen. The educational product of this dissertation presents a didactic guide so that other teachers can develop this theme in Basic Education. [resumo fornecido pelo autor]
Este trabalho de pesquisa apresenta o desenvolvimento e os resultados de uma intervenção pedagógica online no Ensino de Ciências, com estudantes do Ensino Fundamental II, sobre o tema de Astronomia. Escolheu-se o método de Ilhas Interdisciplinares de Racionalidade (IIR), proposto por Fourez (1997), para promover a alfabetização científica e tecnológica (ACT) desses estudantes por meio do Ensino de Astronomia. Esta pesquisa teve como objetivo geral: analisar a aplicação do método de IIR no formato online na promoção do Ensino de Astronomia nos anos finais do Ensino Fundamental. E, como objetivos específicos: promover o Ensino de Astronomia por meio do método de Ilhas Interdisciplinares de Racionalidade; desenvolver os atributos da ACT pelos estudantes: a comunicação, a autonomia e o domínio do tema; e criar um guia para professores sobre o Ensino de Astronomia utilizando o método de IIR, de acordo com os pressupostos da BNCC. As atividades foram desenvolvidas com uma turma de 9o ano, de uma escola do interior do estado do Rio Grande do Sul (RS), durante o ano de 2020. A pesquisa está dentro da linha "Fundamentos e Estratégias Educacionais no Ensino de Ciências e Matemática", proposta no Mestrado Profissional em Ensino de Ciências e Matemática da Universidade de Caxias do Sul. Esta pesquisa é de natureza aplicada, abordagem qualitativa e, em relação aos procedimentos, é uma intervenção pedagógica. Os resultados alcançados, com as atividades desenvolvidas, demonstram que por meio da construção da IIR ocorreu o desenvolvimento dos atributos da ACT por parte dos estudantes: autonomia na execução das atividades, comunicação com os grupos de trabalho e durante as apresentações, e domínio do tema escolhido. O produto educacional desta dissertação apresenta um guia didático para que outros professores possam desenvolver essa temática na Educação Básica. [resumo fornecido pelo autor]
Keywords: Alfabetização; Base Nacional Comum Curricular; Astronomia; Educação; Ensino fundamental; Literacy; Common National Base Curriculum; Astronomy; Education; Elementary School